Unraveling The Relationship Between Kindergartners’ Fine Motor Skills with Their Numeracy Skills (British Journal of Multidisciplinary and Advanced Studies, 2024)
Fine motor skills play a fundamental role in a kindergartner's development, serving as the building blocks for more advanced abilities. The purpose of this descriptive correlational study was to determine the influence of the kindergartners’ fine motor skills on their reading and numeracy skills. The study involved 54 kindergartners who were enrolled in a private school in Cagayan de Oro City, Philippines in the School Year 2022-2023. A checklist from Early Childhood was used to assess the fine motor skills of the kindergartners. A researcher-made instrument was also crafted to assess their numeracy. Frequency, mean, percentage, standard deviation and regression analysis were employed to analyse the collected data. The results revealed that the kindergartners’ fine motor skills need improvement, while the numeracy skills were good. Fine motor skills significantly influence the kindergartners’ numeracy skills indicating that kindergartners with better fine motor skills more likely exhibit good performance on their numeracy skills. The findings suggest that kindergartners have to progress and comprehend numerical concepts. Based on the result of the study, it is recommended that kindergarten teachers may provide remedial instruction or any intervention to assist kindergartners who perform poorly in numeracy skills.